Protocol to measure and analyze protein interactions in mammalian cells using bioluminescence resonance energy transfer - Carla Jane Duval; Candy Laura Steffen; Karolina Pavic; Daniel Kwaku Abankwa (STAR Protocols)
Summary: Bioluminescence resonance energy transfer (BRET) allows to quantitate protein interactions in intact cells. Here, we present a protocol for measuring BRET due to transient interactions of oncogenic K-RasG12V in plasma membrane nanoclusters of HEK293-EBNA cells. We describe steps for seeding, transfecting, and replating cells. We then detail procedures for their preparation for BRET measurements on a CLARIOstar microplate reader and detailed data analysis.For complete details on the use and execution of this protocol, please refer to Steffen et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.